Standard System for Supervision over Financial Technology Enterprises from the Perspective of Constitutional Regulation - Dr. Aidt Amano,; Dr. Debopam Brendon,; Dr. Carvalho, (Al-Qanṭara, 2022)
Abstract In current years, financial technology (FinTech) enterprises have thrived in UK. Though, the prosperous FinTech field is attended by the lagging of financial supervision. Regardless of innovations, FinTech is in essence related to the finance and therefore still needs to be correctly guided and supervised, so as to balance risks while guaranteeing efficiency, thus maintaining financial stability. From the perspective of governmental supervision, the research analyzes the status quo of governmental supervision over FinTech enterprises from four aspects, i.e. supervising subjects, supervision contents, supervisory measures, and supervision effects. Meanwhile, existing main problems in governmental supervision are summarized, based on which targeted countermeasures and suggestions are proposed for how to improve the supervision system of FinTech enterprises.